A thermally stable, printable and LCST-adjustable thermochromic gel and a preparation method thereof and a thermochromic gel coating
By adopting the semi -crossing network skeleton structure in thermal discoloration gel, combined with UV -light cross -linking aggregation technology, the problem of unstable size and response temperature of gels at high temperatures and difficulty adjustment. And the armal deformation gel that responds to the adjustment temperature is suitable for large -scale and pattern applications.
Patent Information
- Application Number
- CN202410964453.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-18
AI Technical Summary
Existing thermochromic gels are unstable in size at high temperatures, difficult to adjust the response temperature, and complex preparation process, making them unable to achieve large-scale and patterned applications.
Sodium carboxymethyl cellulose and N-isopropylacrylamide are mixed according to a specific ratio, a cross-linking agent and a photoinitiator are added, and a thermochromic gel with a semi-interpenetrating network skeleton structure is prepared through UV photo-cross-linking polymerization. .
The thermal stability, printable, and response temperature of the armal discoloration gel has been realized, and the requirements of the human comfortable environmental temperature are met, and it is applicable to large -scale preparation and pattern applications.
Smart Images

Figure CN118702866B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermochromic gels, and in particular to a thermochromic gel that is thermally stable, printable and has adjustable LCST, a preparation method thereof and a thermochromic gel coating. Background Art
[0002] Thermochromic thermosensitive gel materials are widely used in light / heat regulation of smart windows, such as PNIPAM-based gels. So far, the research on PNIPAM-based thermochromic gels in the field of smart windows has mainly focused on enhancing the ability to adjust sunlight, ignoring the importance of response temperature in building thermal management and energy saving. Although, researchers can change the response temperature of the gel to a certain extent by introducing metal ions into the thermosensitive gel or randomly copolymerizing hydrophilic / hydrophobic monomers on the main chain of the responsive polymer. However, both strategies have shortcomings, such as metal ions will aggravate the dimensional instability of thermosensitive gels above the phase transition temperature; random copolymerization will sacrifice the accuracy of the response temperature. In addition, for smart window applications, poor dimensional stability above the phase transition temperature is also another challenge faced by PNIPAM-based thermochromic gel materials, that is, PNIPAM-based thermosensitive gels usually shrink severely at high temperatures (above 35°C). The above two strategies for adjusting the response temperature have little effect on improving the dimensional stability of the gel at high temperatures. To this end, some researchers have increased the thermal stability of the gel by designing an interpenetrating network structure, but this strategy cannot effectively adjust the response temperature of the thermochromic gel. In addition, the traditional synthesis strategy of thermochromic gels such as PNIPAM-based gels induced by thermal initiators usually takes several hours, and most reaction precursors are low-viscosity aqueous solutions, which lack good self-support and cannot be used for large-scale and complex patterning applications.
[0003] In summary, the current thermochromic gel still has the following three shortcomings:
[0004] (1) The thermal response temperature of existing PNIPAM-based thermochromic materials (mostly above 32°C) is higher than the comfortable ambient temperature for the human body (23-28°C), and good energy-saving thermal management cannot be achieved;
[0005] (2) The reaction precursors of existing PNIPAM-based thermochromic materials are mostly low-viscosity aqueous solutions, which must be formed in a closed container when used, and cannot be used on a large scale or in a patterned manner;
[0006] (3) Existing thermochromic materials such as PNIPAM-based materials will dehydrate rapidly when exposed to high temperatures, causing the material to deform significantly and fail to meet the long-term stability requirements of thermal management gels.
[0007] Therefore, at present, there is a lack of a thermally stable, printable and LCST-adjustable thermochromic gel and its preparation technology, which can achieve adaptive light / heat management while having adjustable response temperature and good thermal stability, and is suitable for large-scale preparation and pattern diversity applications. Summary of the invention
[0008] Based on the above-mentioned existing technical problems, the present invention provides a thermally stable, printable and LCST-adjustable thermochromic gel to solve the problems that the existing thermochromic temperature-sensitive gel system has complex components and cannot have good thermal stability, printability and response temperature at a comfortable ambient temperature for the human body.
[0009] To achieve the above object, the present invention provides a thermally stable, printable and LCST-adjustable thermochromic gel, which comprises the following steps:
[0010] S1. Add sodium carboxymethyl cellulose and N-isopropyl acrylamide into water at a mass ratio of (0.1-0.6):1, wherein the amount of water is 5-8 times the total weight of sodium carboxymethyl cellulose and N-isopropyl acrylamide, and mix well to obtain a viscous solution;
[0011] S2, adding a crosslinking agent and a photoinitiator to the viscous solution and mixing them evenly to obtain a reaction precursor solution, wherein the crosslinking agent is N,N-methylenebisacrylamide or divinylbenzene;
[0012] S3. Place the reaction precursor solution at a temperature of 0-10°C and irradiate with ultraviolet light to perform photo-crosslinking polymerization to obtain a thermochromic gel.
[0013] As a further preferred technical solution of the present invention, in step S1, sodium carboxymethyl cellulose and N-isopropyl acrylamide are mixed at a mass ratio of (0.3-0.6):1.
[0014] As a further preferred technical solution of the present invention, the photoinitiator is 2-hydroxy-2-methylpropiophenone.
[0015] As a further preferred technical solution of the present invention, in step S1, the mass ratio of the amount of the cross-linking agent to N-isopropylacrylamide is 1:(200-1000).
[0016] As a further preferred technical solution of the present invention, in step S3, the wavelength of the ultraviolet light is 365 nm, and the ultraviolet irradiation time is 2-5 min.
[0017] As a further preferred technical solution of the present invention, in step S3, the reaction precursor solution is coated to form a film with a thickness of 0.5-5 mm, and then photo-crosslinked polymerization is carried out under ultraviolet light.
[0018] According to another aspect of the present invention, the present invention also provides a thermochromic gel, which is prepared by the above method.
[0019] According to another aspect of the present invention, the present invention also provides a thermochromic gel coating using the above thermochromic gel, which can be applied to smart windows. Specifically, the reaction precursor liquid can be coated with a certain thickness to form a gel film with a preset pattern by means of scraping, 3D printing or screen printing, and then photo-crosslinked and polymerized to form a thermochromic gel coating.
[0020] The present invention selects sodium carboxymethyl cellulose, an easily gelling polymer, to construct a semi-interpenetrating network skeleton, so that it can well disperse and "adsorb and fix" the thermosensitive polymer monomer N-isopropylacrylamide; then, under the induction of ultraviolet light, the thermosensitive polymer monomer distributed in the gel network skeleton undergoes confined polymerization; by adjusting the ratio of the easily gelling polymer to the thermosensitive polymer monomer, the density of the network skeleton in the reaction precursor solution can be changed, thereby affecting the polymerization process of the thermosensitive polymer monomer, and then preparing thermochromic gels with different response temperatures.
[0021] Since the semi-IPN skeleton is an easily gelled polymer, regulating its concentration can also adjust the rheological properties of the reaction precursor liquid to make it appear as a printable gel state. In addition, due to the strong interaction between the semi-IPN skeletons and the non-covalent interaction between the semi-IPN skeleton molecules and the thermosensitive polymer, the semi-IPN skeleton can fully resist the deformation of the thermosensitive polymer inside the skeleton network at high temperatures, achieving good dimensional stability of the gel without affecting the thermochromic process of the gel. For traditional thermochromic thermosensitive gels without network support, the molecular chains curl and shrink violently after heating, resulting in the removal of a large amount of free water, causing the gel volume to shrink.
[0022] Compared with the prior art, the following beneficial effects can be achieved:
[0023] 1) The thermally stable, printable and LCST-adjustable thermochromic gel provided by the present invention is combined with an efficient photopolymerization strategy. By regulating the ratio of easily gelling polymer and thermosensitive polymer monomers and the reaction temperature (0-10 ℃), the response temperature can be adjusted (26.5-30.0 ℃), meeting the most comfortable ambient temperature requirement for the human body.
[0024] 2) The thermally stable, printable and LCST-adjustable thermochromic gel provided by the present invention has high thermal stability and can maintain a stable shape for a long time in an environment above the response temperature.
[0025] 3) The thermally stable, printable and LCST-adjustable thermochromic gel reaction precursor provided by the present invention exhibits good gel properties and can be applied in a patterned manner. It can be coated / printed into any desired pattern as required without flow deformation.
[0026] 4) The thermally stable, printable and LCST-adjustable thermochromic gel provided by the present invention has a simple preparation process, low cost and can be mass-produced and applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0028] Figure 1 The DSC data of the thermochromic gel samples prepared in Examples 1-5 of the present invention and Comparative Example 1 are shown.
[0029] Figure 2 The viscosity data of the thermochromic gel-like reaction precursor solution prepared in Examples 1-5 of the present invention and Comparative Example 1.
[0030] Figure 3 This is a graph showing the shear strain and modulus data of the reaction precursor solution of the thermochromic gel prepared in Example 1 of the present invention.
[0031] Figure 4 The graphs are rheological properties of the reaction precursor solutions of the thermochromic gels prepared in Example 1 of the present invention and Comparative Example 1 under different storage conditions.
[0032] Figure 5 These are digital photos and thermal infrared photos of the heating time and area shrinkage of the thermochromic gel samples prepared in Example 1 of the present invention and Comparative Example 1 on a 40° C. hot stage.
[0033] Figure 6 The data of area shrinkage of the thermochromic gel prepared in Example 1 and Comparative Example 1 of the present invention after being heated on a hot plate at 40° C. for 20 min are statistically shown.
[0034] Figure 7 This is a photo of the thermochromic gel prepared in Example 1 of the present invention being patterned. The thermochromic gel is coated on a glass substrate into a plurality of parallel strips. For ease of observation, green plants are used as the background.
[0035] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0036] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0037] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0038] 1. Study on the mechanism of regulating gel response temperature and thermal stability by regulating the ratio of easy-gelling polymer (sodium carboxymethyl cellulose) and thermosensitive polymer monomer (N-isopropylacrylamide)
[0039] Example 1
[0040] The preparation method of the thermochromic gel which is heat-stable, printable and LCST-adjustable is as follows:
[0041] 90 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the solution, and the solution was fully stirred and dissolved; then 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to the solution in sequence and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C, and a thermochromic gel sample was obtained.
[0042] The reaction precursor solution and the thermochromic gel prepared in this example were tested using the following methods:
[0043] 1) The response temperature of the sample was tested using a differential scanning calorimeter (Q2000, TA Instruments-Waters LLC, USA). Specifically, 5 to 10 mg of the sample was placed in an aluminum crucible, and the temperature measurement procedure was as follows: the equilibrium temperature was set to 20 °C, isothermal at 20 °C for 1 min, and heated from 20 °C to 40 °C at a heating rate of 2 °C / min. The response temperature of the material was determined by observing the change in thermal enthalpy of the material during the heating process. The DSC test results showed that the response temperature of the thermochromic gel prepared in this embodiment was 28.5 °C ( Figure 1 ).
[0044] 2) The viscosity and loss factor of the reaction precursor at different shear rates were tested using a rotational rheometer (MCR302, Anton Paar GmbH, Austria) to evaluate the gelation characteristics of the reaction precursor. The test environment temperature was maintained at 20 °C during the test, and a 1° cone plate with a diameter of 5 cm was selected. The test results are shown in Figure 2. Figure 2 As shown, the reaction precursor solution in this embodiment has a relatively high viscosity. When the shear rate is 1 / s, the viscosity of the reaction precursor solution is 94.6 Pa s -1 , the loss factor is 0.9. In addition, if Figure 3 As shown, the reaction precursor liquid maintains good gel properties under different shear strains, which means that the storage modulus is higher than the loss modulus. It can be seen that the gel property of the reaction precursor liquid gives it good self-supporting properties. Figure 4 It can be seen that at different rotation angles, the reaction precursor liquid can maintain a stable shape in the reagent bottle without deforming and flowing arbitrarily, which further confirms that the reaction precursor liquid has good self-supporting properties.
[0045] 3) In order to observe the dimensional stability of the gel above the phase transition temperature, we placed the prepared gel sample on a 40°C hot stage and used a digital camera and a thermal infrared imager to record the morphological changes and surface temperature changes of the gel within 20 minutes. Finally, we calculated the area change of the gel (the initial temperature of the gel was 20°C) before and after heating, i.e., the area shrinkage rate. The test results are shown in Figure 2. Figure 5 As shown. It can be seen that as the heating time increases, the gel sample prepared in this embodiment can quickly (<1min) undergo a phase change, that is, it changes from the initial transparent to white, and the gel sample can maintain good dimensional stability during the heating process, and its surface temperature is lower than the temperature of the hot stage. According to statistics, the sample was heated at 40°C for 20 min, and the area shrinkage rate was only 5% ( Figure 6 ).
[0046] 4) In order to realize the patterned application of gel, the reaction precursor liquid is patterned on the surface of the base material by means of scraping or the like, and reversible color change can be achieved. A glass plate is selected as the substrate, and a silicone plate with hollow stripes is attached to the surface of the substrate; a certain mass of the reaction precursor liquid is weighed and poured on the silicone plate with hollow stripes, and the reaction precursor liquid is scraped into the hollow stripe pattern with a scraper, and the scraping thickness is 2-3mm. The silicone plate is removed to obtain a glass plate with a gel stripe pattern. At this time, the reaction precursor liquid can adhere well to the surface of the substrate and will not produce flow deformation; the glass plate carrying the patterned gel is placed under ultraviolet light for photo-crosslinking polymerization to obtain a thermochromic gel coating consistent with the above-mentioned stripe pattern. The wavelength of the ultraviolet light is 365 nm, the ultraviolet irradiation time is 3 min, and the reaction temperature is 5 °C. Figure 7As shown, the thermochromic gel coating forming a stripe pattern on the glass plate can maintain the temperature response characteristics well, and can change from transparent to white when the temperature is higher than its phase transition temperature, and return to transparent color when the temperature drops below its phase transition temperature. Moreover, the thermochromic gel coating can always maintain its shape and stably adhere to the glass plate.
[0047] The test methods involved in the following embodiments and comparative examples are the same as those in Example 1.
[0048] Example 2
[0049] The difference from Example 1 is that the amount of sodium carboxymethyl cellulose is changed to 30 mg.
[0050] 30 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution and stirred thoroughly to dissolve to obtain solution B; 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to solution B in sequence and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C.
[0051] According to DSC test, the response temperature of the thermochromic gel prepared in this embodiment is 30.5 ℃ ( Figure 1 ). According to statistics, after heating at 40 ℃ for 20 min, the area shrinkage rate of the gel sample is 33%, and the thermal stability is average.
[0052] like Figure 2 As shown, the reaction precursor liquid in this embodiment has a relatively low viscosity. When the shear rate is 1 / s, the viscosity of the reaction precursor liquid is 1.5 Pa s -1 , the loss factor is 3.4, the reaction precursor liquid does not have good gel properties, the self-supporting property is poor, and part of the reaction precursor liquid coated on the substrate will deform and flow at will.
[0053] Example 3
[0054] The difference from Example 1 is that the amount of sodium carboxymethyl cellulose is changed to 60 mg.
[0055] 60 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution and stirred thoroughly to dissolve to obtain a solution; 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to the solution in sequence and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C.
[0056] According to DSC test, the response temperature of the thermochromic gel prepared in this embodiment is 29.5 ℃ ( Figure 1 ). According to statistics, after heating at 40°C for 20 min, the area shrinkage rate of the gel sample prepared in this embodiment is 16%, and the thermal stability is slightly better.
[0057] like Figure 2 As shown, the reaction precursor liquid in this embodiment has a certain viscosity. When the shear rate is 1 / s, the viscosity of the reaction precursor liquid is 15.7 Pa s -1 , the loss factor is 1.6, still does not have good gel properties, the self-supporting property is poor, but it is stronger than Example 2. The effect of patterned application is general, flow occurs locally, and it is difficult to ensure the integrity of the pattern.
[0058] Example 4
[0059] The difference from Example 1 is that the amount of sodium carboxymethyl cellulose is changed to 120 mg.
[0060] 120 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution and stirred thoroughly to dissolve to obtain a solution; 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to the solution in sequence and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C.
[0061] According to DSC test, the response temperature of the thermochromic gel prepared in this embodiment is 29.5 ℃ ( Figure 1 ), and the phase change time is less than 1 min. According to statistics, the area shrinkage rate of the gel sample prepared in this embodiment is 5% after heating at 40°C for 20 min, and the thermal stability is very good.
[0062] like Figure 2 As shown, the reaction precursor liquid in this embodiment has a certain viscosity. When the shear rate is 1 / s, the viscosity of the reaction precursor liquid is 257.2 Pa s -1 , the loss factor is 0.6, the reaction precursor has good gel properties and good self-support, and can realize patterned applications.
[0063] Example 5
[0064] The difference from Example 1 is that the amount of sodium carboxymethyl cellulose is changed to 180 mg.
[0065] 180 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution and stirred thoroughly to dissolve to obtain a solution; 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to the solution in sequence and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C.
[0066] The DSC test results show that the response temperature of the thermochromic gel prepared in this example is 29.5 ℃ ( Figure 1 ), and the phase change time is less than 1 min. According to statistics, the area shrinkage rate of the gel sample prepared in this embodiment is 3% when heated at 40°C for 20 min.
[0067] like Figure 2 As shown in Figure 2, the reaction precursor has a good viscosity. When the shear rate is 1 / s, the viscosity of the reaction precursor is 1032.4 Pa s -1 , the loss factor is 0.5. The reaction precursor has good gel properties and good self-supporting properties, and can realize patterning applications.
[0068] Furthermore, when the amount of sodium carboxymethyl cellulose is further increased on the basis of Example 5, the viscosity of the reaction precursor solution will be too high, and operations such as printing and scraping cannot be achieved, and the patterned application requirements cannot be met.
[0069] Comparative Example 1
[0070] As a comparative experiment of the above embodiment, a thermochromic gel without sodium carboxymethyl cellulose was prepared as follows:
[0071] 300 mg of N-isopropylacrylamide was weighed and added to 2.5 mL of ultrapure water and stirred thoroughly to dissolve to obtain a solution; 0.5 mg of crosslinking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were added to the solution in sequence and stirred evenly to obtain a reaction precursor solution. The reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 5 °C to obtain a thermochromic gel sample.
[0072] According to DSC test, the response temperature of the thermochromic gel prepared in this comparative example is 31.5° C. The viscosity of the reaction precursor solution in this comparative example is extremely low. Figure 4 As shown in the figure, it can be seen that at different angles, the reaction precursor liquid can deform and flow at will, and has no self-supporting property at all, and cannot be used for printing / patterning applications. Figure 5 As shown in the figure, with the increase of heating time, the gel sample prepared in this case takes a long time (>1 min) to produce phase change from transparent to white, and the dimensional stability of the gel sample is poor. After heating for 2 min, obvious dehydration occurs and severe shrinkage begins. According to statistics, the area shrinkage rate of the gel sample is 52% ( Figure 6 ).
[0073] The parameters and some performances of Examples 1 to 5 and Comparative Example 1 are summarized in Table 1.
[0074] Table 1
[0075]
[0076] 2. Study on the mechanism of regulating the reaction temperature to achieve the gel response temperature
[0077] Comparative Example 2
[0078] The preparation method of the thermochromic gel provided in this comparative example is different from the preparation method in Example 1 only in that the reaction temperature is different. The preparation method comprises:
[0079] 90 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution, and the solution was fully stirred and dissolved to obtain a solution; 0.5 mg of a cross-linking agent N,N-methylenebisacrylamide and 3 mg of a photoinitiator 2-hydroxy-2-methylpropiophenone were sequentially added to the solution and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was -5 °C.
[0080] Since the reaction temperature is too low, the precursor solution cannot react effectively under ultraviolet light, and the gel cannot be formed after the reaction. Even if the illumination time is increased to 1 h, the forming effect is very poor.
[0081] Example 6
[0082] The preparation method of the thermochromic gel provided in this embodiment is different from the preparation method in Example 1 only in that the pre-reaction temperature is different. The preparation method comprises:
[0083] 90 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution, and the solution was fully stirred and dissolved to obtain a solution; 0.5 mg of a cross-linking agent N,N-methylenebisacrylamide and 3 mg of a photoinitiator 2-hydroxy-2-methylpropiophenone were sequentially added to the solution and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 0 °C.
[0084] According to DSC test, the response temperature of the thermochromic gel prepared in this case is 28.5 ℃. For the gel sample obtained after polymerization, it shows high transparency when the temperature is lower than the phase transition temperature. According to statistics, in the thermal stability test, the area shrinkage rate of the gel sample is only 5% when heated at 40 ℃ for 20 minutes.
[0085] Example 7
[0086] The preparation method of the thermochromic gel provided in this embodiment is different from the preparation method in Example 1 only in that the pre-reaction temperature is different. The preparation method comprises:
[0087] 90 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution, and the solution was fully stirred and dissolved to obtain a solution; 0.5 mg of cross-linking agent N,N-methylenebisacrylamide and 3 mg of photoinitiator 2-hydroxy-2-methylpropiophenone were sequentially added to the solution and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 10 °C.
[0088] According to DSC test, the response temperature of the thermochromic gel prepared in this embodiment is 29°C. For the polymerized gel sample, when the temperature is lower than the phase transition temperature, it shows high transparency. According to statistics, in the thermal stability test, when heated at 40°C for 20 minutes, the area shrinkage rate of the gel sample is only 5%.
[0089] Comparative Example 3
[0090] The preparation method of the thermochromic gel provided in this comparative example is different from the preparation method in Example 1 only in that the pre-reaction temperature is different, and the preparation method comprises:
[0091] 90 mg of sodium carboxymethyl cellulose was weighed and dissolved in 2.5 mL of ultrapure water to obtain a solution with a certain viscosity; 300 mg of N-isopropyl acrylamide was added to the above solution, and the solution was fully stirred and dissolved to obtain a solution; 0.5 mg of a cross-linking agent N,N-methylenebisacrylamide and 3 mg of a photoinitiator 2-hydroxy-2-methylpropiophenone were sequentially added to the solution and stirred evenly to obtain a reaction precursor solution; the reaction precursor solution was placed under ultraviolet light for photocrosslinking polymerization to obtain a thermochromic gel, wherein the wavelength of the ultraviolet light was 365 nm, the ultraviolet irradiation time was 3 min, and the reaction temperature was 15 °C.
[0092] According to DSC test, the response temperature of the thermochromic gel prepared in this comparative example is 31°C. For the polymerized gel sample, it will also appear white when the temperature is lower than the phase transition temperature, so it is not conducive to light regulation. According to statistics, in the thermal stability test, the area shrinkage rate of the gel sample is 6% when heated at 40°C for 20 minutes.
[0093] The parameters and partial performances of the above-mentioned comparative examples 2-3 and embodiments 1, 6 and 7 are summarized in Table 2.
[0094] Table 2
[0095]
[0096] In summary, the thermochromic gel obtained by the present invention has good thermal stability, can be used for patterned printing, and has an adjustable response temperature at an ambient temperature comfortable for the human body (23-30°C), so it can be applied in daily human life. For example, the formation of thermochromic gel coatings for use on smart windows has the following advantages: 1) printability, so that the gel precursor liquid can be adhered to the glass substrate in a preset area, thickness, and shape by simple coating means, and the pattern can be kept unchanged before polymerization, so that a series of operations can be carried out before polymerization without affecting the pattern morphology; 2) good thermal stability, in an environment of about 40°C, a small area shrinkage rate is maintained, so that the coverage area of the coating is greatly less affected by changes in ambient temperature, and will not cause the coverage area of the coating on the smart window to be affected in high temperature (about 40°C) weather, and it is not easy to fall off due to shrinkage and deformation; usually, when the ambient temperature is higher than 23-28°C, it is necessary to shade the windows of the building to avoid excessively high indoor temperatures. Otherwise, there is no need to deliberately block the sunlight. The response temperature of the hydrogel of the present invention just meets this requirement, and it is transparent below the response temperature and non-transparent white at high pressure response temperature. In addition, the thermochromic gel of the present invention has a simple composition and convenient performance control. It only needs to mix sodium carboxymethyl cellulose and N-isopropyl acrylamide in a predetermined ratio and photopolymerize them at a certain temperature to meet the requirements without adding other additional functional components. Moreover, the preparation method is simple and low in cost, which is conducive to industrial-scale production.
[0097] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a thermochromic gel that is heat-stable, printable and has adjustable LCST, characterized in that: The following steps are involved: S1. Add sodium carboxymethyl cellulose and N-isopropyl acrylamide into water at a mass ratio of (0.1-0.6):1, wherein the amount of water is 5-8 times the total weight of sodium carboxymethyl cellulose and N-isopropyl acrylamide, and mix well to obtain a viscous solution; S2, adding a crosslinking agent and a photoinitiator to the viscous solution and mixing them evenly to obtain a reaction precursor solution, wherein the crosslinking agent is N,N-methylenebisacrylamide or divinylbenzene; S3. Place the reaction precursor solution at a temperature of 0-10°C and under ultraviolet light for photo-crosslinking polymerization to obtain a thermochromic gel.
2. The method for preparing a thermochromic gel having a heat stability, printability and adjustable LCST according to claim 1, characterized in that: In step S1, sodium carboxymethyl cellulose and N-isopropyl acrylamide are mixed at a mass ratio of (0.3-0.6):
1.
3. The method for preparing a thermochromic gel having a heat stability, printability and adjustable LCST according to claim 1, characterized in that: The photoinitiator is 2-hydroxy-2-methylpropiophenone.
4. The method for preparing a thermochromic gel having a thermal stability, printability and adjustable LCST according to claim 1, characterized in that: In step S1, the mass ratio of the amount of the cross-linking agent to the amount of N-isopropylacrylamide is 1:(200-1000).
5. The method for preparing a thermochromic gel having a heat stability, printability and adjustable LCST according to claim 1, characterized in that: In step S3, the wavelength of the ultraviolet light is 365 nm, and the ultraviolet irradiation time is 2-5 min.
6. The method for preparing a thermochromic gel having a heat stability, printability and adjustable LCST according to claim 1, characterized in that: In step S3, the reaction precursor solution is coated to form a film with a thickness of 0.5-5 mm, and then photo-crosslinked polymerization is performed under ultraviolet light.
7. A thermochromic gel, characterized in that: The method is prepared by any one of claims 1 to 6.
8. A thermochromic gel coating, characterized in that: The thermochromic gel according to claim 7 is used.
Citation Information
Patent Citations
Thermochromic composite material for intelligent window
CN113773599A
Preparation method of gelatin-based thermochromic hydrogel material
CN117209692A